Computer Performance Engineering: 16th European Workshop, EPEW 2019, Milan, Italy, November 28-29, 2019, Revised Selected Papers - Gribaudo, Marco; Iacono, Mauro; Phung-Duc, Tuan; Razumchik, Rostislav (Lecture Notes in Computer Science, 2020)
This book constitutes the refereed proceedings of the 16th European Workshop on Computer Performance Engineering, EPEW 2019, held in Milan, Italy, in November 2019.The 10 papers presented in this volume together with one invited talk were carefully reviewed and selected from 13 submissions. The papers presented at the workshop reflect the diversity of modern performance engineering, with topics ranging from modeling and analysis of network/control protocols and high performance/BigData information systems, analysis of scheduling, blockchain technology, analytical modeling and simulation of computer/network systems.